Przywilej księżnej Katarzyny i jej synów dla Kożuchowa z 1419 roku = The privilege of duchess Catherina and her sons for Kożuchów from 1419 - Karczewska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Kożuchow was one of the important city in the Duchy of Głogow. It was very important in the turn of the XIV and XV century. In that time the Duchy of Głogow was divided into two parts: the Duchy of Kożuchow and Zielona Gora and the Duchy of Głogow. During the reign of duchess - widow Catherina and young princes, the city got some privilegies. The most important one was from 8 I 1419, which confirmed previous privilegies and statute law.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia